Coming to terms - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
With the clock already ticking uncomfortably fast on world trade talks, the CTA seminar on 'Meeting the challenge of effective ACP participation in international trade negotiations' came not a moment too soon, in late November 2002 in Brussels,...